A Chilean Initiative in Favor of the Price of Bolivian Tin (1951-1952). an Economic Issue in the Chilean-Bolivian-United States Relationship; [Una Iniciativa Chilena a Favor del Precio del Estaño Boliviano (1951-1952). Un Tema Económico en la Relación Chile-Boliviaestados Unidos] - Garay-Orellana, C (Ediciones Universidad de Salamanca, 2019)
This article analyzes the initiatives of Chilean President Gabriel González Videla (1946-1952) in favor of the price of bolivian tin in the 1950s as a consequence of a vision that, in the economic sphere, contained critical elements of Washington’s relationship with the South American countries. The novelty of this position is that it contradicts the historiographic consensus on the conflicting nature of relations between Chile and Bolivia and also nuances the idea that Gonzalez Videla’s political alignment should be extended to the field economic. © Ediciones Universidad de Salamanca / cc by-nc-nd.